Radiosonde Data from 2006 NABOS Cruise (International Arctic Research Center (IARC) Data Archive)
Radiosonde data collected in the Russian Arctic on board the 'Kapitan Dranitsyn' during NABOS (Nansen and Amundsens Basins Observational System) 2006. Data submitted by V.Alexeev, collected by P.Minnett of RSMAS, U Miami.